فاعلية برنامج تدريبي قائم على الوظائف التنفيذية في تحسين الصمود التعليمي لدى طالبات الجامعة المعرضات لخطر الإخفاق الأكاديمي - لطفي، أسماء محمد السيد (جامعة الأزهر - كلية التربية, 2024)
هدف البحث إلى التحقق من فاعلية برنامج تدريبي قائم على الوظائف التنفيذية في تحسين الصمود التعليمي لدى طالبات الجامعة المعرضات لخطر الإخفاق الأكاديمي. وشارك في البحث الأساسي (٢٦) طالبة من الطالبات المعرضات لخطر الإخفاق الأكاديمي بالفرقة الأولى بقسم علم النفس بكلية الدراسات الإنسانية بنات جامعة الأزهر بالقاهرة، تم تقسيمهن إلى مجموعتين تجريبية وقوامها (۱۳) طالبة تم تطبيق البرنامج التدريبي عليهن، ومجموعة ضابطة قوامها (۱۳) طالبات لم يتلقين أي تدريب؛ وشملت أدوات البحث مقياس تشخيص التعرض لخطر الإخفاق الأكاديمي في المرحلة الجامعية، ومقياس الصمود التعليمي، ومقياس الوظائف التنفيذية، والبرنامج التدريبي القائم على الوظائف التنفيذية، والأدوات من إعداد الباحثة؛ وأسفرت النتائج عن وجود فروق ذات دلالة إحصائية بين متوسطي رتب درجات طالبات المجموعة التجريبية المعرضات لخطر الإخفاق الأكاديمي على أبعاد مقياسي الوظائف التنفيذية والصمود التعليمي والدرجة الكلية لكل منهما في القياسين القبلي والبعدي في اتجاه القياس البعدي، ووجود فروق ذات دلالة إحصائية بين متوسطي رتب درجات طالبات المجموعتين التجريبية والضابطة المعرضات لخطر الإخفاق الأكاديمي على أبعاد مقياسي الوظائف التنفيذية والصمود التعليمي والدرجة الكلية لكل منهما في القياس البعدي في اتجاه المجموعة التجريبية، وعدم وجود فروق ذات دلالة إحصائية بين متوسطي رتب درجات طالبات المجموعة التجريبية المعرضات لخطر الإخفاق الأكاديمي على أبعاد مقياسي الوظائف التنفيذية والصمود التعليمي والدرجة الكلية لكل منهما في القياسين البعدي والتتبعي؛ تمت مناقشة نتائج البحث في ضوء الإطار النظري والدراسات السابقة، وتقديم بعض التوصيات والدراسات والبحوث المقترحة. The research aimed to verify the effectiveness of a training program based on executive functions in improving educational resilience of female university students at risk of academic failure. (26) female students at risk of academic failure in the first year of the Psychology Department at the Faculty of Human Studies for Girls, Al-Azhar University in Cairo participated in the basic research. They were divided into two groups: an experimental group consisting of (13) female students on whom the training program was applied, and a control group consisting of (13) female students, They have not received any training; The research tools included a scale for diagnosing exposure to the risk of academic failure at university, educational resilience scale, executive functions scale and training program based on executive functions, and tools prepared by the researcher. The results revealed that there were statistically significant differences between the mean ranks of scores of experimental group members of female university students at risk of academic failure on dimensions of executive functions and educational resilience scales, and total score for each of them in the pre- and post-measurements in the direction of the post-measurement, and there were statistically significant differences between the mean ranks of scores of experimental and control groups’ members of female university students who are at risk of academic failure on dimensions of executive functions and educational resilience scales, and total score for each of them in the post-measurement in the direction of the experimental group, and there were no statistically significant differences between the mean ranks of experimental group members’ scores of female university students who are at risk of academic failure on dimensions of executive functions and educational resilience scales, and total score for each of them in the post and follow-up measurements. The research results were discussed in light of the theoretical framework and previous studies, and some recommendations and proposed research were presented.
Keywords: البرامج التعليمية -- الإخفاق الدراسي -- الصمود الأكاديمي -- العملية التعليمية -- طلبة الجامعات